The Effectiveness Of Career Counseling Model Towards Career Maturity Level And Locus Of Control Among Inmates In Rehabilitation Centers - Amin Al Haadi Shafie; Hishamuddin Abdul Wahab; Mohd Khairul Anuar Rahimi; Nurhafizah Mohd. Sukor; Siti Nubailah Mohd Yusof; Nur Fatini Athilah Binti Elias; Nurul Ashikin Binti Ahmat Miskam (Center for Promoting Ideas, 2024)
The aim of this paper is to discuss on the effectiveness of career counseling model toward the level of career maturity and locus of control among the inmates. A Career Therapy Model is carried out, and the results are measured by using Career Maturity Inventory or CMI and ACREDA-Drug-Related-Locus of Control or ACREDA-DRLOC. The results of the CMI test showed that there is a significant increase in the maturity of career planning among those who have undergone the career model (experimental group) than the control group. Whereas, for Locus of Control, the test results showed that there were minor changes to the locus of control experienced by the experimental group. It was concluded that the intervention of career model has given positive impacts as the respondents’ career planning clarity are enhanced and the sense of internal-oriented control are instilled. Keywords: Career Counselling Model, Career Maturity, Locus of Control, Drug Rehabilitation, Career Planning,Employment